"An Unacceptable Surrender of Fiscal Sovereignty": The Neoliberal Turn to International Tax Arbitration. Issue 1 (20th March 2023) - Hearson, Martin; Tucker, Todd N.
Abstract : The growth of inequality over the past half century is closely connected to the rise of neoliberal policies and institutions, the latter of which shield capital from state actions that might limit wealth accumulation. Economic nationalism since the global financial crisis has slowed or even reversed this, yet this same era has seen the emergence of a new form of instrument in the neoliberal mold, in a stronghold of state sovereignty: taxation. Under mandatory binding tax arbitration, states cede sovereignty over the interpretation of international tax agreements to panels of transnational tax adjudicators. Focusing on the pivotal role of the United States, we use historical documents, including from the congressional archive and interviews with key actors to ask why tax arbitration emerged late in the neoliberal era, and at a counterintuitive time. We demonstrate that this outcome is the result of instrumental business power driving a process of incremental change through layering, to overcome states' preference to retain sovereignty. This experience sheds light on the historically structured ways that business power constrains sovereignty in an era of high inequality.